Analisis Prokrastinasi Tugas Akhir/Skripsi - Tatan Zainal Mutakien (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2012)
This research aim to to know factors causing student procrastinate in solving of theses/final duty. Research location in University of Indraprasta PGRI Jakarta. Time Research executed in June - August 2011. Research Sampel counted 80 student of Education of Mathematics Program which is finishing theses. Method which is used in this research is method of survey with technique of deksirptif. Technique analyse used data cover; factor analysis and analysis of hirerarchi process (AHP). Result of factor analysis conclude that there is 3 dominant factor which cause postponement of student in finishing of skripsi; 1) 83.8 % student less is comprehending is way of making of theses, 2) 82.6 % student less is comprehending of eye of study research method, 3) 76.3 % student less is comprehending of eye of studi pre seminar of theses.